Komunikasi Publik Humas Universitas Teknologi Sumbawa dalam Meningkatkan Citra Positif - Hidayat, Ofi; Aggasi, Abbyzar; Cahyani, Destian (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
Public relations is an important part of an institution or institution. The existence of public relations in an institution as part of the task of managing public service information and communication, even in the current digital era, is a major factor in terms of public communication services. Then in educational institutions today, public relations is also the main actor in terms of delivering information and communication to bridge external and internal publics in establishing interactions. Public relations of educational institutions also currently play a role in maintaining and improving the positive image of the institution. So this study aims to look at the practices and activities of public relations at Universitas Teknologi Sumbawa (UTS) in maintaining and improving the positive image of educational institutions. This research uses the Elaboration Likelihood Model (ELM) by looking at the paths used in the message delivery process. The qualitative method is the research approach used by conducting direct observations and interviews so that researchers can directly observe and explore public relations activities. The results of this study revealed that UTS public relations successfully managed the use of information media in providing public communication services. UTS PR uses several stages in the process of conducting public communication services, such as initial research, planning, coordination, and evaluation. UTS public relations are also able to manage information on social media platforms, which are actively used as a medium for distributing information that is well packaged and interesting, so that the activities carried out by UTS public relations are able to improve a positive image for institutions, especially Universitas Teknologi Sumbawa.